The role of serum zinc and MicroRNAs in osteoporosis: insights into bone metabolism and potential diagnostic markers - Parastoo Karimi; Mohammad Reza Mirzaei; Farzaneh Arami; Zahra Bagheri-Hosseinabadi; Mitra Abbasifard; Saeed Mohammadi-Hosseinabad; Zahra Jalali; Mehdi Mahmoodi; Mohammad Reza Hajizadeh (BMC Musculoskeletal Disorders)
Abstract Background Zinc (Zn) levels are reportedly lower in osteoporosis patients and may be linked to bone health. MicroRNAs (miRNAs) have also been implicated in the regulation of bone remodeling. This study aims to investigate the role of selected miRNAs and their potential interplay with Zn in the pathogenesis of osteoporosis. Methods In this case-control study, 50 patients with osteoporosis and 50 healthy controls were recruited. The serum transcript levels of miRNAs were assessed using Real-time PCR. Results Levels of Zn was significantly (P = 0.0047) lower in the serum samples from osteoporosis patients in comparison to the healthy controls. The transcript level of miR-34a-5p (Fold change = 2.59, P = 0.008) and miR-335-5p (Fold change = 1.90, P = 0.013) was upregulated significantly in the serum samples of patients with osteoporosis compared to that of the healthy controls. Zn level in osteoporosis patients had significant negative correlation with transcript levels of miR-335-5p (r= -0.24, P = 0.037). Zn level had positive correlation with Z and T-scores and BMD of hip, spine, and femur. A negative correlation (r= -0.28 P = 0.044) was detected between transcript level of miR-34a-5p and femur BMD. There was a significant negative correlation between transcript level of miR-335-5p and hip BMD (r= -0.19 P = 0.038). miR-34a-5p and miR-335-5p showed diagnostic potential. Conclusions The findings suggest a potential interplay between Zn and miRNAs in the regulation of bone metabolism in osteoporosis patients. Zn and miRNAs may serve as biomarkers for bone health and a therapeutic target in osteoporosis management.